Ultra-hypofractionated radiotherapy for low- and intermediate risk prostate cancer: High-dose-rate brachytherapy vs stereotactic ablative radiotherapy. (May 2021) - Tsang, Yat Man; Tharmalingam, Hannah; Belessiotis-Richards, Katherine; Armstrong, Shreya; Ostler, Peter; Hughes, Robert; Alonzi, Roberto; Hoskin, Peter J
Highlights: This study reported treatment outcomes for prostate cancer patients receiving ultra-hypofractionated radiotherapy using high dose-rate brachytherapy (HDR BT) and stereotactic ablative radiotherapy (SABR). 26 Gy/2 fractions HDR BT provided equivalent biochemical disease control with lower toxicity compared to 36.25 Gy/5 fractions SABR. Both 2-fraction HBR BT and 5-fraction SABR achieved better biochemical disease control than single dose 19 Gy HDR BT. Abstract: Purpose: To compare the biochemical control rates (BCRs), late gastrointestinal (GI) and genitourinary (GU) toxicities in patients with low- and intermediate risk prostate cancer (PCa) treated with high-dose-rate brachytherapy (HDR BT) of 19 Gy/1 fraction, 26 Gy/2 fractions, or stereotactic ablative radiotherapy (SABR) of 36.25 Gy/5 fractions. Methods and materials: Between August 2008 and December 2017, patients with low- and intermediate risk PCa who received single dose or 2-fraction HDR BT, or 5-fraction SABR at a single institution were included. BCR for the whole population and the individual treatment groups were calculated using the Phoenix definition. Post treatment GI and GU toxicities were evaluated according to the CTCAE v4.0 guidelines. Results: 185 patients with low- and intermediate risk PCa were included in this study with a median follow up of 60.5 months. BCRs at 3 and 5 years were 95% and 85% for all patients. The 5-year BCRs were 69%, 95% and 92% for the 19 Gy/1 fraction, 26 Gy/2 fractions and 36.25 Gy/5 fractions groups respectively. The cumulative 5-year incidence rates of ≥grade 2 GI events in the 19 Gy/1fr, 26 Gy/2fr and 36.25 Gy/5fr groups were 0%, 2% and 4%, respectively. Incidence rates in those treated in the 5-fraction SABR arm were significantly higher ( p  < 0.05) than those treated in both HDR BT arms where no statistically significant difference between the two HDR BT groups was seen ( p  = 0.15). The cumulative 5-year incidence rates of ≥grade 2 GU events in the 19 Gy/1fr, 26 Gy/2fr and 36.25 Gy/5fr groups were 30%, 5% and 6%, respectively. No statistically significant difference was found between the 26 Gy/2fr and 36.25 Gy/5fr ( p  = 0.37) treatment arms but the incidence rate in the 26 Gy/2fr were significantly lower than those seen after 19 Gy/1fr ( p  < 0.05). Conclusions: 26 Gy/2 fractions HDR BT provided equivalent BCR with lower toxicity compared to 36.25 Gy/5 fractions SABR. Both 2-fraction HBR BT and 5-fraction SABR achieved better BCRs than single dose 19 Gy HDR BT. The two-fraction HDR BT schedule should be considered as an important comparator in future clinical trials.